2020
DOI: 10.1371/journal.pone.0240982
|View full text |Cite
|
Sign up to set email alerts
|

Metformin partially reverses the inhibitory effect of co-culture with ER-/PR-/HER2+ breast cancer cells on biomarkers of monocyte antitumor activity

Abstract: Background Immune activities of monocytes (MOs) can be altered within the microenvironment of solid malignancies, including breast cancer. Metformin (1,1-dimethylbiguanide hydrochloride, MET), has been shown to decrease tumor cell proliferation, but its effects have yet to be explored with respect to MOs (monocytes) activity during their crosstalk with breast cancer cells. Here, we investigated the effects of MET on overall phenotypic functional activities, including cellular immunometabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Interestingly, the evaluation of the expression of Arg-1 revealed the opposite responses of THP-1 monocytes to external stimuli within the tested co-cultures. The study by Dahmani et al revealed that the phenotypic functional activities of monocytes were modified after co-culturing with primary human breast cancer cells [ 43 ]. In the presence of MCF-7 but not MDA-MB-231 cells, THP-1 cells showed a strong decrease in the expression of Arg-1 when compared with monocytes cultured alone.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the evaluation of the expression of Arg-1 revealed the opposite responses of THP-1 monocytes to external stimuli within the tested co-cultures. The study by Dahmani et al revealed that the phenotypic functional activities of monocytes were modified after co-culturing with primary human breast cancer cells [ 43 ]. In the presence of MCF-7 but not MDA-MB-231 cells, THP-1 cells showed a strong decrease in the expression of Arg-1 when compared with monocytes cultured alone.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with high-grade serous EOC exhibit the phenotype of defective HR without BRCA mutations known as “BRCAness” [ 33 ]. Metformin is a low-toxicity therapeutic approach that targets various key pathways and is crucial for cancer treatment [ 34 ]. Metformin has been used for over 60 years, whereas olaparib is a relatively new drug that has been used as part of chemotherapy since the beginning of 2015.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical trials, PARPis significantly increased the efficacy of standard therapies through combination treatment with carboplatin (NCT01033292), cediranib (NCT02681237), or nivolumab (NCT03522246). In breast cancer cells, metformin induces cell death via PARP activation and apoptosis [ 33 ], and in ovarian cancer, it induces cell death in combination with other drugs such as cisplatin [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of HER2 + breast cancer cells co‐cultured by monocytes with metformin showed a decline in the IL‐10 release, while stimulates the release of IFN‐γ. However, the levels of Arginase (a marker of TAMs) were upregulated following treatment with metformin (Dahmani et al 2020). Although the modulatory effect of metformin in this study isn't favorable for tumor therapy, we should consider that metformin may affect the expression of iNOS + macrophages in a complete tumor model, because of the release of inflammatory cytokines by CTLs and NK cells.…”
Section: Metformin and Tamsmentioning
confidence: 99%